Development and implementation of strategies for further development of confectionery manufacturers - on the example of JSC "LCF "SVITOCH" - Nataliia Kuzo; Nаtaliia Kosar; Yaryna Yarychevska; Olga Oprysk (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2021)
In a changing marketing environment, each enterprise should predict strategies for its further development, the implementation of which often involves the development of new products. At the same time, this allows the company to increase its competitiveness in the market. The purpose of this article is to study the confectionery industry of Ukraine, the needs of consumers in them, and justify proposals for a new product within the framework of the strategy for the further development of the confectionery enterprise (on the example of JSC "LCF "Svitoch"). When writing this work, methods of generalization of theoretical sources in the field of formation of strategies for the development of the enterprise in the market, comparison, statistical analysis, surveys, SWOT analysis, and expert evaluations were used. The results of the survey show that JSC "LCF "Svitoch" successfully carries out activities in the domestic confectionery market. The conducted swot analysis allows us to conclude that this confectionery manufacturer should focus on the use of an intensive and diversifying growth strategy in the future. To implement the strategy of intensive development of JSC "LCF "Svitoch", significant marketing efforts should be made in improving certain components of its marketing complex. The strategy of diversification growth is aimed at expanding the product range of this enterprise with new products, such as dried fruits or sweets for children, other goods. The results of the consumer survey and expert survey indicate that JSC "LCF "Svitoch" should expand its range due to sweets with a low sugar content, namely sweets with fruit fillers.